Ozone disc nucleolysis as an alternative to open disc surgery for slip disc - Sardar, K; Das, G; Mahta, P; Mallick, S; Hubbard, R (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Back pain associated with herniated disks has become an important and increasing general health problem, both in Bangladesh and across the world. After all methods of conservative treatment have been exhausted, nucleolysis may be a minimally invasive alternative to surgery. In nucleolysis, chondrolytic substances, or other substances which reduce the pressure within the disk by other means, are injected into the nucleus pulposus under CT or C-arm guidance. Among various substances, which have been employed for nucleolysis, an ozone-oxygen mixture appears to be very promising. The water-binding capacity of ozone results in a reduction of pain. Moreover, it has an anti-inflammatory effects and results in an increase of perfusion to the affected area. Ozone is converted into pure oxygen in the body and has a low allergic potential. Recent minimally invasive therapeutic methods such as percutaneous nucleotomy or laser treatment have not been shown to result in superior results compared with ozone nucleolysis. JBSA 2012; 25(1): 32-35